Merger Waves and the Austrian Business Cycle Theory (2014)
This paper identifies merger waves as parts of Austrian-type business cycles. According to Austrian business cycle theory, when loan rates are reduced below their natural level through bank credit expansion, this falsifies the monetary calculation of capitalist-entrepreneurs, and investments are initiated that calculation showed were not profitable before the interest rate reduction. Since there are not enough resources in the economy to complete the new projects, businesses must increasingly withdraw the resources from other companies. Thus, this paper concludes that the increase in investment activity and the resulting “resource crunch” cause a merger wave that helps prolong the boom phase of the cycle. The merger wave ends when the credit expansion is not sufficient to sustain the economic boom, and the bust phase begins. Conversely, this paper concludes that if the fiduciary media do not enter the economy through the loan market to finance business investment, there is no pronounced and sustained increase in merger activity.